Corporate finnancial insolvency forecast based on proyected fuzzy classification. A methodology de analysis - Castiblanco, Fabián Alberto; Sánchez, Deisy Nohemí (2021)
The timely detection of business insolvency is of interest to society, both for the protection of their economic interests and the preservation of trust, and to minimize the impacts caused by the liquidation of a company. Likewise, the relative trend of viability or risk of business failure constitutes an indicator of the strength of the industries and of the economy as a whole.